2019
DOI: 10.1002/chem.201903909
|View full text |Cite
|
Sign up to set email alerts
|

A Coumarin Triflate Reagent Enables One‐Step Synthesis of Photo‐Caged Lipid Metabolites for Studying Cell Signaling

Abstract: Photoreleaseo fc aged compoundsi sa mong the most powerful experimentala pproaches for studying cellularf unctions on fast timescales. However, its full potential has yett ob ee xploited, as the number of caged small molecules available for cell biological studies has been limited by synthetic challenges. Addressing this problem, as traightforward, one-step procedure fore fficiently synthesizing caged compounds was developed.A n in situ generated benzylic coumarin triflate reagent was used to specifically func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Photocaged lipids have emerged as attractive strategy for the photoactivation of lipids through cleavage of a photosensitive protection group to reveal the native lipid . Photocaged versions of phosphatidic acid , have been used to control the activation of matrix metalloproteinase 2 and flagellar excision . Chemical modifications of the photosensitive groups also allow for subcellular targeting. …”
Section: Introductionmentioning
confidence: 99%
“…Photocaged lipids have emerged as attractive strategy for the photoactivation of lipids through cleavage of a photosensitive protection group to reveal the native lipid . Photocaged versions of phosphatidic acid , have been used to control the activation of matrix metalloproteinase 2 and flagellar excision . Chemical modifications of the photosensitive groups also allow for subcellular targeting. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schultz and co-workers reported a photocaged version of LPA that allowed for light-induced activation of LPA receptor-dependent effects, including chemotaxis . However, photoactivation of this probe is not reversible, and it has a chemically modified headgroup, which perturbs the amphiphilic character of the molecule and might affect trafficking. , In recent years, we and others have developed a series of photoswitchable lipids and demonstrated their capacity for the reversible optical control of lipid metabolism and signaling. These photoswitchable lipids have an azobenzene photoswitch incorporated into the hydrophobic tail and mediate optical control of lipid function by reversible, light-induced isomerization between the trans - (straight) and cis - (bent) isomers.…”
mentioning
confidence: 99%
“…Reagent stability was a concern since only a single functionalization reaction involving a benzylic triflate reagent had been reported before . Nevertheless, upon generation of DEAC-triflate in situ and direct use of the reaction mixture for the functionalization reaction, we found that native lipids could indeed be selectively equipped with a photocaging group at the phosphate or carboxylate moieties . We demonstrated the utility of this transformation for a number of potent G-protein-coupled receptor (GPCR) ligands, including lysophosphatidic acid, platelet activating factor, and prostaglandin E2.…”
Section: Main Textmentioning
confidence: 98%
“… 2019 25 15483 15487 . 3 Show the in situ synthesis of diethylaminocoumarin-triflate to directly functionalize native lipids with a photocaging group at the phosphate or carboxylate moieties. Live-Cell Lipid Biochemistry Reveals a Role of Diacylglycerol Side-Chain Composition for Cellular Lipid Dynamics and Protein Affinities Schuhmacher M. Grasskamp A. T. Barahtjan P. Wagner N. Lombardot B.…”
Section: Key Referencesmentioning
confidence: 99%